(untitled) (Research, Society and Development, 2021)
The present research is about the high performance teams and the leader. Work teams have effectively become a goal in the institutional world, at present these teams have garnered emphasis on their performance and the effect of this has been found to be useful in developing effective and high performance teams. So he wondered, what is the role of the leader as a builder and evaluator of performance in high performance teams? Sustained by the hypothesis that the leader has the role of motivator, evaluator, manager in the high performance teams. The research aims to understand the different theoretical conceptions about high performance teams and to observe the role of the leader as a builder and performance evaluator. In order to answer the proposed objective, we used a qualitative deductive wedge bibliographic research. The results indicate that the leader enables the development and growth of the team, and stimulates conflict resolution, participation, correlation of knowledge, skills and actions that come from its components, favoring that these teams are competent and become a differential for the institution. It turns out that institutions need to adopt team structures that focus on performance and a leader capable of guiding the direction to high performance.